Mutation of Hashimoto’s Thyroiditis and Papillary Thyroid Carcinoma Related Genes and the Screening of Candidate Genes - Zhang, Lizhuo; Zhou, Lingyan; Feng, Qingqing; Li, Qinglin; Ge, Minghua (Frontiers in Oncology, 2021)
Clinical studies have shown similarities in the genetic background and biological functional characteristics between Hashimoto's thyroiditis (HT) and papillary thyroid carcinoma (PTC), and that HT may increase risks of PTC. Here, we set to determine the gene expression specificity of HT and PTC by screening related genes or co-expressed genes and exploring their genetic correlation. Referencing the Oncomine database, HT-related genes were discovered to be expressed in many different types of thyroid cancer, such as TSHR that is highly expressed in thyroid cancer. An in-depth genetic analysis and verification of 35 cancer and paracancerous tissue pairs from patients with thyroid cancer, and 35 tissues and blood cells pairs from patients with Hashimoto's thyroiditis was conducted. Gene chip technology research showed that TSHR, BACH2, FOXE1, RNASET2, CTLA4, PTPN22, IL2RA and other HT-related genes were all expressed in PTC, in which TSHR was significantly over-expressed in PTC patients sensitive to radioactive iodine therapy, while BACH2 was significantly under-expressed in these patients. The biologically significant candidate Tag SNP highlighted from HT-related genes was screened by the high-throughput detection method. Somatic mutations in patients with HT and PTC were detected by target region capture technique, and 75 mutations were found in patients with HT and PTC. The upstream regulatory factors of the different genes shared by HT and PTC were analyzed based on Ingenuity Pathway Analysis (IPA), and it was found that HIF-1α and PD-L1 could be used as important upstream regulatory signal molecules. These results provide a basis for screening key diagnostic genes of PTC by highlighting the relationship between some HT-related genes and their polymorphisms in the pathogenesis of PTC.